2004
DOI: 10.1099/mic.0.27144-0
|View full text |Cite
|
Sign up to set email alerts
|

New roles for CDC25 in growth control, galactose regulation and cellular differentiation in Saccharomyces cerevisiae

Abstract: Living organisms display large differences in stress resistance throughout their life cycles. To study the coordinated regulation of development and stress responses in exponentially growing yeast, mutants that displayed elevated heat-shock resistance at this stage were screened for. Here, two new mutant alleles of CDC25 in Saccharomyces cerevisiae, cdc25-21 and cdc25-22, are described. During exponential growth in glucose at 25 6C, these mutants are resistant to heat, oxidative, osmotic and ionic shock, accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The results of this study are in agreement with recent studies that revealed the existence of dual-function regulators that can participate in controlling both cell proliferation and differentiation (50). In Saccharomyces cerevisiae, CDC25 has been found to contribute growth control galactose regulation and cellular differentiation (51). In Caenorhabditis elegans, DNA damage checkpoint proteins have been found to control survival of the postmitotic cells (52).…”
Section: Figuresupporting
confidence: 91%
“…The results of this study are in agreement with recent studies that revealed the existence of dual-function regulators that can participate in controlling both cell proliferation and differentiation (50). In Saccharomyces cerevisiae, CDC25 has been found to contribute growth control galactose regulation and cellular differentiation (51). In Caenorhabditis elegans, DNA damage checkpoint proteins have been found to control survival of the postmitotic cells (52).…”
Section: Figuresupporting
confidence: 91%
“…The common functions of Wee1 and Cdc25 in the yeasts are also found in the smut fungus Ustilago maydis, in which both the Wee1 overexpression and the Cdc25 inactivation led to specific G2 arrest that correlated with the high level of Cdk1 phosphorylation at Tyr 15 (Sgarlata and Pérez-Martín, 2005a,b). Aside from an involvement in cell cycle, Cdc25 has proved to participate in the regulation of yeast cell responses to heat, oxidation, high osmolarity and ionic shock (Folch-Mallol et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another cascade starts with Ras2 and Cdc25 instead of Rga1. These proteins work together and are important for the exit from a G0 state (52). Along with Cdc28 they allow the G1/S transition by increasing Cln2 levels (53).…”
Section: Discussionmentioning
confidence: 99%